2016
DOI: 10.1007/s11096-016-0349-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring discharge prescribing errors and their propagation post-discharge: an observational study

Abstract: Background Discharge prescribing error is common. Little is known about whether it persists post-discharge. Objective To explore the relationship between discharge prescribing error and post-discharge medication error. Setting This was a prospective observational study (March-May 2013) at an adult academic hospital in Ireland. Method Patients using three or more chronic medications pre-admission, with a clinical pharmacist documented gold-standard pre-admission medication list, having a chronic medication stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
1
26
1
Order By: Relevance
“…The definition of a DRP was provided in six studies [53,56,58,76,79,81] out of the cohort of 27 studies that mentioned outcome definitions. Error categories were mentioned in 14 studies [23, 24, 60, 61, 65, 70-72, 75, 81, 85, 87, 90, 97] but were only defined in five studies [60,72,75,85,87]. The outcome denominator was clearly defined in all papers and the data collection method was described clearly in all but one study [91].…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The definition of a DRP was provided in six studies [53,56,58,76,79,81] out of the cohort of 27 studies that mentioned outcome definitions. Error categories were mentioned in 14 studies [23, 24, 60, 61, 65, 70-72, 75, 81, 85, 87, 90, 97] but were only defined in five studies [60,72,75,85,87]. The outcome denominator was clearly defined in all papers and the data collection method was described clearly in all but one study [91].…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…In total, 12 studies [23,65,71,72,75,85,87,89,90,96,97,99] reported data concerning the frequency of MEs. Six studies used established definitions of MEs [23,71,72,75,85,87], with one study developing their own definition [90], and five not reporting any definition [65,89,96,97,99]. Five studies [71,72,87,90,97] reported data specifically concerning prescribing errors, of which two [72,87] used the prescribing error definition proposed by Dean et al [101].…”
Section: Medication Error Studiesmentioning
confidence: 99%
See 3 more Smart Citations